Tick-borne encephalitis virus variants drive distinct TCR repertoire alterations - Salnikova, Maria A.; Tuchynskaya, Ksenia K.; Minervina, Anastasia A.; Pogorelyy, Mikhail V.; Okhezin, Egor V.; Karganova, Galina G.; Mamedov, Ilgar Z.; Lebedev, Yuri B. (Frontiers in Immunology, 2025)
BackgroundT cells play a crucial role in the adaptive immune response against acute virus infections. The extensive diversity of T cell receptors (TCRs) presents a complex challenge for understanding its implications in immune responses. Investigating the dynamics of the immune response to acute virus infection is inherently more complex compared to studying vaccine responses, but it offers a more comprehensive view on the subject matter.MethodsTherefore, we used an immunosequencing approach to investigate acute viral infections in a murine model system. Specifically, we analyzed the TCRβ repertoire to identify dissimilarities in the immune response of BALB/c mice against different variants of tick-borne encephalitis virus (TBEV), which differ by a few amino acid substitutions and are derived from the same parental strain.ResultsWe identified numerous TCRβ clonotypes that responded to the infection. Furthermore, we observed differences in the magnitude of the T cell response depending on the virulence of either the TBEV variant or the immature TBEV particles. Interestingly, regardless of the viral variant, we observed a shift towards CD8+ T cells among TBEV-associated T cells. Additionally, our findings revealed that TBEV induced massive alterations in through the most represented T cell clones, leading to TCRβ repertoire rearrangement.ConclusionWe were able to identify sequence similarities among TBEV responding clones in mice infected with different virus variants. These findings provide valuable insights into the dynamics of T cell responses during acute viral infections and highlight the importance of studying TCR diversity for an in-depth understanding of the immune response.